Emotional intelligence, work-life balance and job stress / Amirul Hadi Mohd Jailani - Mohd Jailani, Amirul Hadi (Faculty of Business and Management, 2018)
Job stress occurs when there is no proportion between employees’ wants, job requirements, resources, and needs. Statistically, job stress has various consequences for both employee and employer. In this research paper, the researcher tends to study about job stress and the method to decrease or overcome this problem.